High strain, < 001 >-textured Pb(Mg1/3Nb2/3)O3–Pb(Yb1/2Nb1/2)O3–PbTiO3 piezoelectric ceramics. (1st March 2016) - Duran, Cihangir; Dursun, Sinan; Akça, Erdem
Abstract: 0.62[0.75(Pb(Mg1/3 Nb2/3 )O3 )–0.25(Pb(Yb1/2 Nb1/2 )O3 )]–0.38(PbTiO3 ) ceramics were successfully textured in [001] (Lotgering factor of 0.91) using plate-like BaTiO3 templates, for the first time. Samples were densified to 98% of the theoretical density. Significantly higher levels of strain (0.33%) and low-field (< 5 kV/cm) d33 coefficient (1340 pm/V) together with a narrower hysteresis level (7.7%) at 50 kV/cm have been achieved in the textured ceramics. These results are very promising for high performance transducer and actuator applications without severe temperature restriction due to their higher Tc values (214 °C) and also open up new opportunities for the concept of domain engineering in the textured ceramics. Graphical abstract: Texturing results in enhanced anisotropic physical properties in 0.62[0.75(Pb(Mg1/3 Nb2/3 )O3 )–0.25(Pb(Yb1/2 Nb1/2 )O3 )]–0.38(PbTiO3 ) ternary ceramics.